Ni and NixCoy alloys electrodeposited on stainless steel AISI 316L for hydrogen evolution reaction - Gomez, Melisa Julieta (2018)
NixCoy electrocatalysts for hydrogen evolution reaction (HER) were synthesized by electrodeposition on AISI 316L stainless steel (denoted as SS316L), as a scalable and economical alternative to be used in alkaline electrolyzers. For this, a previous treatment of the SS316L surface was carried out in order to optimize the deposition of different catalytic films containing Ni and NixCoy with different compositions (Ni89Co11, Ni69Co31, and Ni29Co71). The properties of the catalysts were established by scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), and X-ray diffraction (XRD), and the catalytic activity for HER was evaluated by potentiodynamic experiments in 1 M KOH solutions. An increase in the current density toward the hydrogen evolution reaction was found with these NixCoy electrodes. For the Ni69Co31 catalyst, current density values 112% higher than those recorded with deposited Ni from conventional Watts bath were obtained. The HER current shows a strong dependence on the content of Co on the alloy that is also evidenced in the electrochemical impedance experiments. The efficiency of electrocatalytic activity for HER was increased after an electrochemical aging treatment, indicating the presence of an activation process, for example with Ni89Co11 electrodes, where higher current density for HER was observed.